Contemplation-based Learning: An Effective Learning Model for Serving Science and Self-Knowledge Integration - Rina Delfita; Ridwal Trisoni; Andrizal Andrizal; Aidhya Irhash Putra; Adripen Adripen (AT-TA'LIM, 2020)
The study aims to produce feasible a contemplation-based learning model based on the aspect of validity and practicality for Biology prospective teachers. Research and development (RD) using ADDIE model was used where the participants in this study were three Biology Education lecturers, three experts, and 35 students who enroll at first semester at Biology Education department in Batusangkar State Islamic Institute (IAIN) as experimental subjects. The instruments used is observation, interview and questionnaire. Means and standard deviations were calculated for finding the level of validity and practicality of the prototype. The results showed that contemplation-based biology learning model meet the characteristics of the learning model and characteristic of contemplation. The contemplative approaches used through deep reading essays and paid attention to figures related to the subject matter of General Biology courses. The values cultivated are values contained in the subject matter. The values that contained in the material are islamic values, it is alasma’ ul husna. The contemplation-based learning model developed is feasible to be applied in the biology classroom with the most valid and very practical category. Thus, the contemplation-based learning model is a solution for overcoming the gap of serving science with self-knowledge and is an alternative learning model to integrate science and religion at Biology Education Department.